Einsatz intermittierender Hypoxie in Sport und Training - Burtscher, M. (Herzfrequenzvariabilität: Gesundheitsförderung - Trainingssteuerung - Biofeedback. Internationales Symposium am 29. und 30. Oktober., 2011)
Whereas intermittent hypoxia (IH) in obstructive sleep apnea is generally associated with adverse effects, some well defined protocols of IH have been used beneficially in sports and training.